Understanding bias better: a qualitative exploration of bias in advisory councils of EU agencies - Bastiaan Redert; Peter Bursens (Political Research Exchange)
European Union (EU) agencies are known to have a high risk of capture by regulated business interests. To limit this risk, agencies try to involve a diverse set of stakeholders. One way of doing so, is to install advisory councils (ACs): permanent bodies with a fixed number of stakeholders selected by the agency. Current scholarship has mainly studied whether stakeholders’ access to ACs is biased towards business interests. However, it remains unknown whether the ACs functioning might also be biased. This research note presents a strategy to go beyond access and look inside the ACs. By examining how members perceive the councils, its meetings and the discussions therein, it explores whether the councils’ functioning contributes to more balanced interest representation. We illustrate that although the councils’ members are willing to prioritize seeking consensus over defending their own interests, finding this consensus proves difficult due to asymmetries in resources, thus stressing the need for a better understanding of bias. We end with proposing further qualitative approaches to study bias of advisory bodies in the future.